2010
DOI: 10.1073/pnas.1002472107
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mismatch repair and genomic stability by miR-155

Abstract: Inactivation of mismatch repair (MMR) is the cause of the common cancer predisposition disorder Lynch syndrome (LS), also known as hereditary nonpolyposis colorectal cancer (HNPCC), as well as 10-40% of sporadic colorectal, endometrial, ovarian, gastric, and urothelial cancers. Elevated mutation rates (mutator phenotype), including simple repeat instability [microsatellite instability (MSI)] are a signature of MMR defects. MicroRNAs (miRs) have been implicated in the control of critical cellular pathways invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
212
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(225 citation statements)
references
References 46 publications
11
212
2
Order By: Relevance
“…miR-155 has been assigned the status of an oncogenic miRNA, because it induces genomic instability, 13,14 and elevated expression levels are observed in hematological 4,5,17 as well as different types of solid tissue cancer. [6][7][8][9] Sustained proliferation is a hallmark of transformed cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-155 has been assigned the status of an oncogenic miRNA, because it induces genomic instability, 13,14 and elevated expression levels are observed in hematological 4,5,17 as well as different types of solid tissue cancer. [6][7][8][9] Sustained proliferation is a hallmark of transformed cells.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9] miR-155 is localized within an exon of its precursor gene BIC (B cell integration cluster or pri-miR-155). 4 Transiently elevated expression of miR-155 plays a role in the activation of several types of immune cells, 2,[10][11][12] whereas constitutively high levels of this miRNA can result in the development of malignancies by increase of genomic instability 13,14 and sustained proliferation and survival 5,15 of malignant cells. Thus, miR-155 is often referred to as a "bridge between inflammation and cancer."…”
Section: Introductionmentioning
confidence: 99%
“…They used the global profiling method [21][22][23][24][25][26][27][28][29] or the candidate miRNA approach [30][31][32][33][34][35][36] and showed that aberrant expression of miRNAs has been associated with tumor histology, [26][27][28] response to steroid therapy 24 or chemotherapy 29 and survival. 21,22,25 However, most studies determined miRNA expression in either normal endometrial tissues or cancer tissues, and the possible miRNA expression in endometrial hyperplasia is largely unknown.…”
mentioning
confidence: 99%
“…miRNAs have been shown to regulate diverse cellular processes, including the DNA mismatch repair (MMR) pathway [12][13][14], a major genome maintenance system. The importance of MMR in genome maintenance is demonstrated by the fact that defects in the system cause genome instability and susceptibility to human cancers [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, precise regulation of the cellular level of MLH1 is critical for genome stability. Although miRNAs likely play an important role in regulating MLH1 expression [12][13][14], the mechanism of the regulation reaction is unclear. Interestingly, recent studies suggest that MLH1 may modulate miRNA processing, as MLH1 expression determines miRNA expression patterns in colorectal tumors [27,28].…”
Section: Introductionmentioning
confidence: 99%